Clinical Outcomes Following the Use of Archived Proviral HIV-1 DNA Genotype to Guide Antiretroviral Therapy Adjustment. (14th December 2019) - Ellis, Kristen E; Nawas, George T; Chan, Connie; York, Lawrence; Fisher, Julia; Connick, Elizabeth; Zangeneh, Tirdad T
Abstract: Background: Evidence regarding the safety of using proviral HIV-1 DNA genotype (DNA GT) to guide antiretroviral therapy (ART) is limited. We hypothesized that HIV RNA would not increase following ART adjustment guided by DNA GT in a university HIV clinic. Methods: Data were obtained from electronic medical records of adult persons living with HIV-1 (PWH) who underwent DNA GT testing and changed ART between October 2014 and November 2017. Logistic regression was used to evaluate the effect of ART switch on HIV RNA over time. Results: Eighty-three PWH had DNA GT performed, 66 (80%) switched ART, and 59 had postswitch follow-up. Data were analyzed pre-/postswitch for these 59 PWH (median age, 54 years; 71% LWH ≥10 years; 46% ≥2 previous regimens; 36% recent low-level viremia; 34% unknown medication history). On DNA GT, 58% had ≥1-class ART resistance, 34% ≥2-class, and 10% 3-class. Median follow-up (range) was 337 (34–647) days. There was no change in probability of HIV RNA ≥50 copies/mL over time ( P  > .05). At baseline, 76% had HIV RNA <50 vs 88% at last postswitch follow-up ( P  = .092). Protease inhibitor use decreased from 58% to 24% ( P  < .001). Average daily pills and dosing frequency decreased from 3.48 to 2.05 ( P  < .001) and 1.39 to 1.09 ( P  < .001), respectively; ART cost did not change. Conclusions: DNA GT facilitated changes in ART in a treatment-experienced population without increases in HIV RNA. Decreased pill burden occurred without increased ART cost. Further studies to identify optimal use of DNA GT are needed.